Performance Evaluation of a Full-Scale Fused Magnesia Furnace for MgO Production Based on Energy and Exergy Analysis - Tianchi Jiang; Weijun Zhang; Shi Liu (Energies, 2021)
A three-electrode alternating current fused magnesia furnace (AFMF) with advanced control technology was evaluated by combined energy and exergy analysis. To gain insight into the mass flow, energy flow and exergy efficiency of the present fused magnesia furnace, the exergy destruction was analysed to study the energy irreversibility of the furnace. Two different production processes, the magnesite ore smelting process (MOP) and light-calcined magnesia process (LMP), are discussed separately. Two methods were carried out to improve LMP and MOP; one of which has been applied in factories. The equipment consists of an electric power supply system, a light-calcined system and a three-electrode fused magnesia furnace. All parameters were tested or calculated based on the data investigated in industrial factories. The calculation results showed that for LMP and MOP, the mass transport efficiencies were 16.6% and 38.3%, the energy efficiencies were 62.2% and 65.5%, and the exergy destructions were 70.5% and 48.4%, respectively. Additionally, the energy efficiency and exergy efficiency of the preparation process of LMP were 39.4% and 35.6%, respectively. After the production system was improved, the mass transport efficiency, energy efficiency and exergy destruction were determined.